Efficacy and safety of acupuncture therapy for chronic atrophic gastritis: A meta-analysis and trial sequential analysis protocol. Issue 35 (August 2019) - Li, Yuan; Zhang, Yili; Meng, Han; Liao, Mengting; Su, Zeqi; Zhai, Mengyin; Jiang, Lingling; Li, Ping; Ding, Xia
Abstract: Background: The proportion of application of acupuncture for chronic atrophic gastritis (CAG) is increasing over time. We will conduct this study to explore the efficacy and safety of acupuncture as a treatment method for CAG. Methods: We will go through domestic and foreign databases until July 2019 to identify related randomized controlled trials that explored the effectiveness of acupuncture for CAG. RevMan (V.5.3) and test sequential analysis (V.0.9) will be used for mata-analysis and trial sequential analysis. Results: This study will update previous evidence summaries of acupuncture and determine the efficacy and safety of acupuncture for CAG based on clinical effectiveness rate, clearance of Helicobacter pylori ( H pylori ) infection, and quality of life and symptom scores. Conclusion: This study will determine the evidence for judging whether acupuncture provides benefits in the treatment of CAG, and will support the application of acupuncture in the recovery of patients with CAG. Registration number: CRD42019127916.